Birds and mammals of Mount Banahaw de Tayabas, Luzon Island, Philippines with notes on their distribution along elevational gradients (Asia Life Sciences : the Asian International Journal of Life Sciences, 2010)
A total of 111 birds and 31 mammals were recorded from five study sites on Mount Banahaw de Tayabas (2,158 m above sea level), the highest peak on Mount Banahaw-San Cristobal Protected Landscape in Laguna-Quezon Provinces, Luzon Island, Philippines. The extremity in elevation allows the formation of a wide range of habitats along different elevational gradients. Distinct groups of birds and mammals were found to inhabit different elevational gradients, with different highland and lowland forms as well as disturbance gradients. Endemicity was high with 50 birds and 16 mammals known to be endemic to the Philippines, with a greater number of endemic found on less disturbed sites and on sites found in higher elevations. These differences in bird and mammal fauna along elevational and disturbance gradients need to be considered in developing monitoring and management plans for these mountain ecosystems. Mount Banahaw de Tayabas contains 30 threatened and rare birds and mammals, which makes it an important refuge for endangered wildlife found in Southern Luzon. However, despite its protected area status, Mount Banahaw-San Cristobal National Park still suffers from various forms of human disturbance, and more appropriate measures of protection are needed to conserve its rich biological diversity.